Medical microbiology - Murray, Patrick R (Mosby, 1998)
Medical Microbiology provides a balanced, up-to-date, clinically relevant introduction to microbiology. It focuses on the microbes that cause disease in humans, and includes important facts and explanations. Hundreds of color photographs and drawings, summary boxes, and tables reinforce the key points. A consistent chapter format is used to discuss the etiology, epidemiology, host defenses, identification, diagnosis, prevention, and control of all the microbial diseases. These factors combine to create a succinct, focused, attractive, and easy-to-follow textbook that is gaining in popularity with each edition.Organized taxonomically, presenting organism groups and taxonomic subdivisions within each group Approximately 500 full-color illustrations and over 400 tables and summary boxes Chapters are small for easy conceptualization with a consistent format Case studies provide scenarios, followed by a series of questions.
Keywords: Communicable Diseases; parazitární nemoci; mikrobiologie, lékařská mikrobiologie; mikrobiologie; Parasitic Diseases; Mikrobiologie; infekční nemoci; Microbiology